Agrobiodiversity conservation practices and gender consideration in Sinana District, southeastern Ethiopia - Asseffa, W. (Madda Walabu University, 2016)
Agricultural biodiversity have significant role in food security, environmental protection, income generation and cultural values and many conservation activities are performed by women but no recognition is given to them as important contributors. Many conservation activities are performed by women but due to unbalanced decision making roles in resource allocation, monocropping has increased from time to time resulting into decrease in nutritious crops, income diversification and increase in environmental problems (like soil and air pollution due to the use of high insect and pest side). The study was carried out in Sinana district, south east of Ethiopia between November 2015 to June, 2016 to investigate agrobiodiversity practices and the role of gender in its conservation. A sample of 364 respondents was selected using simple random sampling technique from four kebeles (villages). Using a semi structured questionnaire, data were collected from 182 female respondents, of which, 91 were married women and 91 female household heads; and 182 were male household heads. In addition twelve focus group discussions (FGDs) were conducted with farmers’ (three groups per kebele) Data were analyzed using SPSS version 20 software to generate descriptive statistics. Chi-square was used to analyze the participation level in agricultural activities by women and men. Pearson correlation was used to test the relationship between gender, age, land size, land ownership and diversity. In addition Simpson’s index (D) = (1-∑ Pi2) also used to identify the diversity of plants and animals that are used by women and men. The results show that rural women, cultivate and domesticate more diversified crops/plants and livestock respectively than men on their land holding. Women participated in all farming activities including decision making, land preparation, seed selection, crop management (weeding, storing, pest control), harvesting and selling commodities and animal domestication. But their participation level has significant Variation on each activity performed in agricultural (P=0.01), and also crop diversity by using Simpson’s index (agricultural diversity on men’s land = 0.864) and that for women’s land =0.84), which plays a great role in conserving agricultural diversity. So there is need to create opportunities for rural women to improve their level of participation and decision making in farming activities for conserving agricultural diversities through well organized and integrated awareness creation, experience sharing, promoting women’s work, identifying constraints and exposing women to different simple technologies.